PREFERENSI SISWA EFL TERHADAP GURU BAHASA INGGRIS YANG BAIK - Setiadi, Muhammad Ikhsan; Febriyanti, Emma Rosana (BASIS (Bahasa dan Sastra Inggris), 2023)
The process of teaching is a continuous learning journey, even with years of experience in teaching English as a foreign language, it is difficult to determine how to be an effective teacher. Different learners and teachers have also different views on what constitutes a "good English language teacher”. The aims of this study are to investigate and identify the qualities and characteristics that make an English teacher competent, as perceived by learners, particularly in the post COVID-19 and to gain insights into how learners' preferences may have evolved or changed due to the challenges and experiences faced during the pandemic, and how these factors influence their evaluation of effective English teachers. The participants in this study are students enrolled in the English Department of FKIP Lambung Mangkurat University Banjarmasin, spanning one batch which is 2020 with total 49 respondent students as participants. Data was collected at the sixth semester using a quantitative descriptive method this was employed to assess the students' feedback using a survey tool adapted from research conducted by Wichadee (2010) and Zamani and Angahari (2016). The questionnaire using close-ended question based on a four-point Likert scale. Total there are 60 statements and it divides from 4 categories (Socio-affective, Pedagogical Knowledge, Proficiency Skills Organization and Communication Skills) and there are 15 statements for each category. Based on the result, the most considered as prominent from the other category is Organization and Communication Skills, as many 82% respondents agreed that teacher should have good competencies especially in good communication skills. The anticipated findings of this study can assist teachers in self-reflection, evaluation, and the enhancement of their teaching practices. Additionally, it can contribute to their personal growth.